Antimicrobial Resistance: Challenges and Perspectives. Issue 2 (11th March 2013) - Doyle, Michael P.; Loneragan, Guy H.; Scott, H. Morgan; Singer, Randall S.
Abstract In 2006, the Institute of Food Technologists (IFT) published an Expert Report entitled "Antimicrobial Resistance: Implications for the Food System" (IFT 2006). That report summarized current scientific knowledge pertaining to the public‐health impact of antimicrobial use in the food system and the development and control of antimicrobial resistance. Since that time, intense interest in this topic has continued within the regulatory and scientific communities as well as the general public. This IFT Scientific Status Summary serves to update that 2006 IFT Expert Report by briefly reviewing new scientific evidence relevant to the goals of the initial report and providing a number of key observations and conclusions.